A study on the need for a comprehensive Law on landlord and tenant (retail tenancy) in peninsular Malaysia. - Syed Abdul Kader, Sharifah Zubaidah; Kassim, Salina; Mohamad, Nor Asiah; Amin, Naemah (INPEN (NAPREC Grant), 2016)
The research project is an exploratory socio-legal research to find out whether there is a need for a comprehensive law governing Landlord and Tenant in retail tenancies in Peninsular Malaysia. There is no retail tenancy law that governs this relationship in Malaysia, unlike the position in Australia and the United Kingdom. In these jurisdictions, it has been accepted that there is inequality of bargaining power between the landlord of a retail premises and its tenant and so the law should, to a certain extent, interfere into this relationship. Another feature of retail tenancy law is the dispute resolution provisions that allow retail tenancy disputes to be settled through alternative dispute resolution mechanisms like mediation.The research employed both, quantitative and qualitative research methods. The quantitative aspect was carried out through questionnaires administered to landlords and tenants of retail premises in the Klang Valley. As most shopping centres had only one landlord, the numbers of landlords sampled were only four while the number of tenants reached 42 from 3 shopping centres and shop lots in a housing area. To further fortify the findings from the survey, the researchers carried out three case studies, a focused group discussion and structured interviews, all of which formed the qualitative part of this study.The findings reveal that there are various issues and problems arising out of the relationship of landlord and tenant of retail premises in the Klang Valley, for both landlord and tenant and that both generally favour proposals to improve this relationship. Retail landlords in Malaysia are usually management companies (on behalf of owners who are REITs companies), public listed companies or GLCs. The majority of tenancies are for a period of three years and below. This research has found that a majority of respondents are agreeable to a special mediation body in settling disputes relating to landlord and tenants in retail premises so as to avoid court action. Further, a large proportion of respondents are also supportive of a specific law to regulate relationship between landlords and tenants.